Activation of human leukocytes by lipid A from E. coli strains adapted to quaternary ammonium salt and amine oxide - Dubnicková, M; Bukovský, M; Mlynarcík, D (Folia microbiologica, 2003)
The immunomodulatory activities of monophosphoryl lipid A (MLA) and diphosphoryl lipid A analogues obtained from the sensitive strain of E. coli and from the resistant strains adapted to a quaternary ammonium salt and an amine oxide were compared. All analogues considerably stimulated the activity of human leukocytes although the analogue from the sensitive strain at a higher concentration significantly suppressed phagocytosis. The MLA analogue exhibited a suppressive effect on the microbicidal activity of human leukocytes against E. coli and the peroxidase activity. Adaptation of bacteria to amphiphilic antimicrobial compounds, which is accompanied by chemical changes in their lipid A, only slightly reduced their immunomodulatory activity when compared with the analogue from the sensitive strain. On the other hand, the diphosphoryl analogues were less active than MLA.
Keywords: Quaternary Ammonium Compounds; Phagocytosis; bakteriální léková rezistence; Leukocytes; Drug Resistance, Bacterial; kvartérní amoniové sloučeniny; Peroxidase; muramidasa; lipid A; fagocytóza; Muramidase; Escherichia coli; Humans; Lipid A; peroxidasa; Dimethylamines; leukocyty; dimethylaminy; lidé